Sistem Informasi Akuntansi Penggajian Dalam Upaya Meningkatkan Efektivitas pengendalian Internal di Yayasan Daarul Muttaqien - Pertiwi, Yunita; Diyani, Lucia Ari (JURNAL MAHASISWA BINA INSANI, 2023)
This research is motivated by the importance of payroll issues at the Foundation, because if the implementation goes well, a good reciprocal relationship will be created, which will increase the productivity of employee performance. The purpose of this research is to analyze and implement an effective payroll accounting information system to increase the effectiveness of internal control. This type of research is descriptive research. The data collection procedure used in this research is to conduct interviews and observations. The results of the study found that: The accounting information system and internal control of employee payroll have not gone well, because there is no payroll flowchart so there are deficiencies in payroll functions, documents and procedures as well as all payroll activities have not been computerized. The elements of the payroll accounting information system have not been effective, have not met the elements of internal control, lack of sound practices because payroll activities have not been computerized so there is a lack of authorization for record keeping supervision.